Understanding Information Literacy Skills and Competencies for Undergraduate Students: A Review of the Literature - Jamila, Usman; Maidabino, A. A. (MiddleBelt Journal of Library and Information Science, 2020)
The paper provides a review on the concept and significance of information literacy. Different typologies of information literacy are also provided in line with the different submissions of the body of knowledge. The paper also gives an in-depth analysis literature on the roles of university libraries in inculcating the necessary information literacy skills to undergraduate students as important information users. The paper further identifies the specific information literacy skills and competencies required by undergraduate students in order to effectively and efficiently utilize the ever-growing information in the digital age.